The Effect of Using Reading Narrative Text as the Vocabulary Learning Strategy on the 11th Grade Students’ Vocabulary Acquisition - Saputri, Refika Nanda; Mardiyana Devanti, Yeni; Nuraini, Kristi (ENJEL: English Journal of Education and Literature, 2025)
Vocabulary is a fundamental aspect for language learners, including English as a foreign language in Indonesia. To master the four language skills (speaking, reading, listening, and writing), the main thing is to fulfil vocabulary. This quantitative research, with a pre-experimental one group pre-test and post-test design, will explore the theory and application of the strategy proposed by Brown and Payne 1994. The research aims to see the extent to which reading narrative texts as a vocabulary learning strategy (VLS) can affect the 11th grade students’ vocabulary acquisition. Data collection will be done through a 22-item multiple-choice vocabulary test as the target vocabulary and given at the beginning of the research (pre-test), as well as at the end after the treatment (post-test). The sample of this research were 28 students of the 11th grade class B SMA Muhammadiyah 2 Wuluhan. The data obtained is analysed using statistical analysis with tests using SPSS version 27.0.1. The results of this study showed a significant effect after implementing reading narrative text as the vocabulary learning strategy on the 11th grade students’ vocabulary acquisition. It is hoped that the results of this research can make a meaningful contribution to the existing literature on the effects of using reading narrative texts as a vocabulary learning strategy on students' vocabulary acquisition, and implement the concept in their teaching practice